POSSIBILITIES OF ACQUIRING COMPETENCIES IN DISEASE MANAGEMENT OF CHILDREN WITH DIABETES MELLITUS - Čergelytė – Podgrušienė, Indre; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Diabetes Mellitus is a chronic disease that occurs as a metabolic disorder. Children often have type 1 diabetes, which occurs when pancreas produces very little or no insulin. Type 1 diabetes may negatively affect the normal lifestyle of a child, as well as his/her development, learning results and growth. It is emphasised that it is important for a child to adjust insulin doses based on the consumed food, physical workload and mental strain; therefore, in this case, the child must be aware of diabetes in order to achieve the most optimal health. The subject-matter of research is the opportunities of children with Diabetes Mellitus to acquire competences for the management of their disease. The aim of research is to disclose how children with diabetes acquire competences for the management of their disease and what opportunities they have for such acquisition. The objectives of research are as follows: 1) to discuss what kind of trainings are being provided to children with diabetes in Europe and Lithuania; 2) to disclose which competences help children with diabetes to manage their disease the most based on their experience. Methods of research – theoretical, such as analysis, generalisation and structuring of scientific literature; empirical, such as semi-structured interview used to collect data; and content analysis method used to analyse the obtained research data. 6 children with Diabetes Mellitus participated in this research. The age of the research participants ranged from 10 to 13 years. During the empirical research, it was disclosed that the most important competences of children with diabetes, allowing/enabling them to manage their disease consist of the correct injection of insulin, proper consumption of food and their abilities to manage hypoglycaemia and hyperglycaemia.